Relevance of the work environment for the fulfillment of the organizational objectives - Davies Oré, Elizabeth Estela (2022)
Currently, the work environment is one of the factors that companies consider most relevant for the achievement of their organizational objectives. Furthermore, over time the interest that the organizations have shown in having not only highly qualified personnel at all their hierarchical levels has been observed and also seeks and encourages them to manifest and put in practice their soft skills. It is precisely these skills that play an important role within them since, apart from creating a good work environment, they lead the entire human team towards the fulfillment of the organizational objectives. At this point, the organization must be very clear and precise when informing them and ensure that these are clearly understood by the staff since these also have to be congruent with the personal and development objectives of all its members.